2014
DOI: 10.1016/j.ijgo.2014.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Severe maternal morbidity and near miss due to postpartum hemorrhage in a national multicenter surveillance study

Abstract: PPH frequently leads to severe maternal morbidity. A surveillance system can identify the main causes of morbidity and could help to improve care, especially among women identified as being at high risk of PPH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 24 publications
1
28
3
1
Order By: Relevance
“…They were organized in two research groups. The first refers to two articles from the "Nascer no Brasil" ("Born in Brazil") study, 5,34 the second reports 13 articles from the Multicenter Study of the "Rede Nacional de Vigilância de Morbidade Materna Grave" [35][36][37][38][39][40][41][42][43][44][45][46][47] ('National Surveillance Network on Severe Maternal Morbidity"). All articles of national scope used the WHO criteria for near miss.…”
Section: National Hospital Based Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…They were organized in two research groups. The first refers to two articles from the "Nascer no Brasil" ("Born in Brazil") study, 5,34 the second reports 13 articles from the Multicenter Study of the "Rede Nacional de Vigilância de Morbidade Materna Grave" [35][36][37][38][39][40][41][42][43][44][45][46][47] ('National Surveillance Network on Severe Maternal Morbidity"). All articles of national scope used the WHO criteria for near miss.…”
Section: National Hospital Based Studiesmentioning
confidence: 99%
“…The aspects that differ from the methodology of the study are shown in Table 2, along with each of the 13 articles. Cecatti et al 35 present overall results, and the other articles explore MNM according to age group 36 and with specific conditions: abortion, 37 ectopic pregnancy, 38 hypertensive diseases, 39,40 hemorrhage, 41,42 infections, 43,44 heart diseases. 45 Healthcare factors were also analyzed, such as quality of care 46 and the association with cesarean section 47 based on Robson's Classification.…”
Section: National Hospital Based Studiesmentioning
confidence: 99%
“…A surveillance study conducted in 27 obstetric units in Brazil found the maternal near miss ratio to be 2.2 per 1000 women with PPH [3]. Wagner et el.…”
Section: Introductionmentioning
confidence: 99%
“…The hereditary risk of retained placenta across generations has to our knowledge not been previously studied. This disorder is emerging as one of the main causes of severe postpartum haemorrhage and near‐miss maternal mortality . Our results indicate that awareness of family history with regard to this complication may be useful in identifying women at risk of postpartum haemorrhage.…”
Section: Discussionmentioning
confidence: 75%
“…Retained placenta is an obstetric complication occurring in approximately 3% of deliveries and associated with severe postpartum haemorrhage (PPH) . There is no certain preventative or non‐invasive treatment for this disorder .…”
Section: Introductionmentioning
confidence: 99%